Beyond the Ode to Joy? The Politics of the European Anthem. Issue 3 (20th June 2019) - Farrington, Conor
Abstract: Anthems are conventionally viewed as helping to unify and mobilise populations by generating a sense of shared identity. Beethoven's Ode to Joy, which currently serves as the European anthem, occupies a more equivocal place in the European Union's symbolic armoury. Whether performed with or without Schiller's original text, the piece raises important questions regarding the nature of the European Union and the purpose of Beethoven's music within contemporary European politics. Nevertheless, given that any practical alternatives also raise significant difficulties, Beethoven's Ode to Joy can be regarded as a useful prompt for reasoned discussions regarding the future of the European Union, especially if reunited with the text of Schiller's An die Freude .